Generalization of the aerodynamic characteristics of the cyclone and vortex chambers during their functioning - Pitak, Inna; Shaporev, Valery; Pitak, Oleg; Briankin, Serhii; Vasyliev, Mykhailo (Technology audit and production reserves, 2017)
The object of research is cyclone and vortex chambers. Dust collectors in the form of cyclones and vortex chambers are promising for studying the process and improving their designs. One of the most problematic areas is the purification of aerodisperse systems, high hydraulic resistance, complex operation and installation, the need for powerful blowing devices. The methods used to clean aerodisperse systems from dust, fog and harmful impurities, and the required purification efficiency are determined by sanitary and technological requirements. They also depend on the physicochemical properties of the impurities themselves, on the composition and activity of the reagents, and on the design of the devices used for purification. In connection with this, various technologies and methods of purification are used. During the research: − analysis of the state of the theoretical description of the processes of «dry» purification of aerodisperse systems and known structures is performed; − analysis of methods for calculating the degree of gas purification from dust; − it is proved that modern methods of calculation don’t take into account some parameters, namely: the characteristic structure of the swirling flow; extinction of the swirling intensity as the flow is removed from the swirler; changes in gas density in the radial direction under the action of centrifugal mass forces; changes in the distribution of dispersed particles in size after passage of the air-dispersed system of swirlers; − it is suggested to consider in the calculations and studies the dust purification device as a complex; − it is proved that the proposed design most fully reflects the features of the process of «dry» purification of the dust and gas flow; − an equation is obtained which allows to estimate the tangential component of the rotation velocity of aerodisperse systems in a cyclone; − it is proved that the tangential component of the rotation velocity of the aerodisperse systems in the vortex apparatus varies depending on the intensity of the vortex and its attenuation. Due to the study of flow dynamics, it is possible to increase the degree of flow purification, to improve the design of the dust purification equipment.